QUALITY OF WORK LIFE, JOB SATISFACTION, AND PERFORMANCE: A MEDIATION ANALYSIS - Venesia, Venesia (Bina Bangsa International Journal of Business and Management, 2025)
This research aims to determine the influence of quality of work life on job satisfaction, the influence of quality of work life on employee performance, the influence of job satisfaction on employee performance, and the influence of quality of work life on employee performance through job satisfaction. This research method is a quantitative method with a population of thirty-seven employees at PT Pelabuhan Indonesia II (Persero) in Pontianak. The data collection technique is saturated sampling (census), the sample used is thirty-seven respondents where the author distributed questionnaires to all employees. From the calculation of the validity test, all variables are valid. The results of the reliability test also show that all instruments used by the researcher are reliable. The results of the hypothesis test show that quality of work life does not have a significant effect on job satisfaction, quality of work life does not have a significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance by 66.10 percent, then quality of work life does not have a significant effect on performance through job satisfaction. Based on the mediation effect test, it is stated that the research model does not have a mediation effect.